CONGENITAL HERNIAS OF THE DIAPHRAGM IN CHILDREN - Mandhan, Parkash; Memon, Aslam; Memon, A Sattar (Journal of Ayub Medical College Abbottabad, 2007)
Background: Congenital diaphragmatic hernia (CDH) is a major congenital malformation. Different types have been described. Bochdalek hernia (BH) remains most prevalent with high mortality rates. Other variants are less common and carry good prognosis. Although, the diagnosis can be made antenatally, the presentation may be delayed. There is paucity of national literature on CDHs. We present our experience with these challenging paediatric malformations. Methods: Medical records of 18 patients (£14 years) treated by the group of authors between October 1998 and April 2002 were retrospectively reviewed and demographic data, clinical presentation, morbidity and outcome were studied. Results: There were 13 (72%) children with Bochdalek hernia, 2 (11%) with eventration of the diaphragm, 2 (11%) with hiatus hernia and 1(6%) with a Morgagni hernia. The lesions were more common in girls and all the defects were left sided. The average age at the time of presentation of BH was 23 hours (2 to 72 hours) commonly presenting with cyanosis and respiratory distress. Associated anomalies were documented in 10 (77%) cases; six had multiple malformations and four died before surgery. In other types of CDHs, the mean age at presentation was 39 (18-60) months and they mostly presented with recurrent respiratory tract infections and/or mild gastrointestinal symptoms. Diagnosis was made on history, physical examination, plain x -ray chest, and gastrointestinal contrast study, when required. 14 (78%) children were operated and a sac was present in 5. Post-operative complications occurred in 5 (55%) patients with Bochdalek hernia, which were managed conservatively. The overall survival rate was 67% (n=12). Conclusion: The different types of CDHs presented from neonatal age to later childhood with distinct symptoms. Surgery was safe and effective. Higher morbidity and mortality was observed in newborns with Bochdalek hernia. Keywords: Congenital diaphragmatic defects; Bochdalek hernia; Congenital diaphragmatic eventration; Morgagni hernia; Hiatus hernia